Некои размислувања за мик. pa-si-te-o-i, 'на сите богови' - Дуев, Ратко (Živa Antika & The Faculty of Philosophy, Skopje, 2012)
What was pa-si-te-o-i used to designate in the Knossos tablets? Of the 16 recipients of olive oil most frequently used are the designations “to all gods” and qe-ra-si-ja. The biggest quantities were offered to qe-ra-si-ja, but the quantity is doubled to “all gods”. Many sanctuaries are mentioned, so the offerings to “all gods” were made in Knossos and in Amnissos in certain months. Although this poses a problem because Zeus and the other gods are not the only ones mentioned, like on the Knossos tablet Fp(1) 1 + 31, it is possible that it resembles Homer’s use of the formula. The question as to why they occur on Crete, and not on the land again resembles Homer’s description. Also, this portrays the connection between the Minoan culture and Asia Minor.
Some thoughts on myc. pa-si-te-o-i, ‘to all gods’